Investigations of surface morphology and chemical composition of Ag/ZnS/glassceramic thin-film structure - Kurbatov, D.; Opanasyuk, A.; Denisenko, V.; Kramchenkov, A.; Zaharets, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The surface morphology and chemical composition of Ag/ZnS/glassceramic
thin-film system obtained by close-spaced vacuum sublimation technique under different
grow conditions were investigated. Examination of surface profile and morphology was
performed by scanning electron and optical microscopy. Chemical composition was
studied by Rutherford back scattering method. Results of morphology studies enabled to
determine dependence of the growth mechanism, roughness Ra, grain size D of ZnS
layers on the growth conditions. The researches of chemical composition allowed to
determine the concentration of compound elements and impurities, deviation from
stoichiometry and thickness distribution of chemical elements.